Cicatricial Alopecia Related to Folliculotropic Mycosis Fungoides - Katharina M. Kreutzer; Isaak Effendy (Adis, Springer Healthcare, 2020)
Abstract Folliculotropic mycosis fungoides (FMF) is a particular subtype of mycosis fungoides (MF), characterized by an infiltration of neoplastic CD4+ T cells in the epidermis which can spread to all follicular structures, sebaceous glands, sweat glands and hair follicles. Clinically, FMF can exhibit various cutaneous symptoms. However, these symptoms often occur on the scalp, face and neck, which are rarely affected by conventional MF. We report cicatricial alopecia in a patient with FMF as alopecia lymphomatica. This peculiar symptom should be kept in mind as a critical differential diagnosis of scarring alopecia, leading to further investigation. Thus, an early diagnosis of FMF may be obtained.